11sin^2 a + 9cos^2 a + 8sin^4 a + 2cos^4 a = = 9sin^2 a + 9cos^2 a + 2sin^2 a + 6sin^4 a + 2(sin^4 a + 2cos^4 a) = (*) Заметим, что 1) 9sin^2 a + 9cos^2 a = 9(sin^2 a + cos^2 a) = 9 2) sin^4 a + cos^4 a = sin^4 a + 2sin^2 a*cos^2 a + cos^4 a - 2sin^2 a*cos^2 a = = (sin^2 a + cos^2 a)^2 - 2sin^2 a*cos^2 a = 1 - 1/2*(4sin^2 a*cos^2 a) Подставляем (*) = 9 + 2sin^2 a + 6sin^4 a + 2 - 4sin^2 a*cos^2 a = = 11 + 4sin^2 a - 2sin^2 a + 6sin^4 a - 4sin^2 a*cos^2 a = = 11 - 2sin^2 a + 6sin^4 a + 4sin^2 a*(1 - cos^2 a) = = 11 - 2sin^2 a + 6sin^4 a + 4sin^4 a = 11 - 2sin^2 a + 10sin^4 a = = 10(sin^4 a - 2*1/10*sin^2 a + 1/100) - 1/10 + 11 = = 10(sin^2 a - 1/10)^2 + 109/10 Минимальное значение квадрата равно 0, а всего выражения 109/10.
СЛОЖЕНИЯ
А)2Х-3У=1
3Х+У=7
УМНОЖИМ ВТОРОЕ УРАВНЕНИЕ НА (+3)
2Х-3У=1
9Х+3У=21
СКЛАДЫВАЕМ
11Х=22
Х=22\11
Х=2
ТОГДА
2Х-3У=1
2*2-3У=1
4-3У=1
-3У=1-4
-3У=-3
У=1
ответ (2,1)